Non-STEM Students in Undergraduate Science: A Global Bibliometric Review Toward Sustainable Development Goal 4 (2017–2025) - Mangubat, Florieza M.; Mangubat Jr, Fernando N. (Universitas Negeri Semarang, 2025)
This bibliometric study analyzes 31 Scopus-indexed publications on non-STEM students in undergraduate science programs from 2017 to 2025, covering 23 sources and reporting an annual growth rate of 9.06% in research output. Using Biblioshiny and VOSviewer, the study examines publication trends, citation performance, collaboration structures, and thematic patterns. The earliest article in 2017 has a mean citation count of 27.44 per year, and the overall collaboration index indicates that multi-authored papers predominate, reflecting moderate to high co-authorship intensity in this niche field. Results show that the United States leads in publication volume and citation impact, followed by Hong Kong, Germany, Brazil, and China, while most other countries contribute only 1 or 2 articles. A small group of authors, institutions, and journals accounts for a large share of documents and citations, indicating a concentrated authorship and source structure. Keyword and thematic analyses reveal that research is primarily organized around course-level themes such as performance, engagement, and teaching approaches, with equity-, gender-, and policy-related topics emerging only in recent years as smaller, low-density clusters. These findings provide a baseline for understanding how research on non-STEM learners in science programs is distributed across authors, outlets, countries, and themes, and where further empirical work is needed to broaden and deepen this research area.